2009
DOI: 10.1007/s00249-009-0540-z
|View full text |Cite
|
Sign up to set email alerts
|

A nonlinear model of ionic wave propagation along microtubules

Abstract: In our recent paper (SatariT et al. 2009), the Introduction section contained statements regarding the C-terminal tails that have inadvertently been included without properly citing the source of this information provided. In particular, the passage given below should be attributed to Georgiev et al. (2004) who almost 5 years earlier correctly pointed out the importance of the C-terminal tail sequence and structure. "Each tubulin monomer of the MT lattice has a short C-terminal helix H12 followed by a highly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…Binding [ 3 H]palmitic acid by microtubules is a known method of identification of tubulin palmitoylation (Caron, 1977;Ozols and Caron, 1977;Hemsley et al, 2008). Microtubules might function as electric transmission lines through ionic propagation (Satarić et al, 2009). DGAT1 and DGAT2 present in the vicinity of a lipid body phospholipid monolayer are indispensable in lipid synthesis.…”
Section: Microtubules and Lipid Synthesismentioning
confidence: 99%
“…Binding [ 3 H]palmitic acid by microtubules is a known method of identification of tubulin palmitoylation (Caron, 1977;Ozols and Caron, 1977;Hemsley et al, 2008). Microtubules might function as electric transmission lines through ionic propagation (Satarić et al, 2009). DGAT1 and DGAT2 present in the vicinity of a lipid body phospholipid monolayer are indispensable in lipid synthesis.…”
Section: Microtubules and Lipid Synthesismentioning
confidence: 99%
“…It has also been explained earlier why the inductance of MTs seen as the transmission line can be safely ignored (15). Based on the experimental findings of Minoura and Muto (22) we estimated the resistivity of an elementary ring to be on the order of 1GΩ: This has been established based on the effective circuit diagram in the context of Kirchhoff's laws constructed for a repetitive arrangement of elementary rings of an MT considered as a ladder-like line, Figure 4.…”
Section: Microtubules (Mts) As Polyelectrolytes Acting As Electric Trmentioning
confidence: 86%
“…Relying on a few experimental assays (21,22), which indicated that the presence of MTs in cytosolic solution increases its ionic conduction, we earlier established an original model which predicts the propagation of signaling ionic impulses along MTs in the form of solitons (15,16,19). We here briefly reexamine this concept in order to apply it for MTs contained in the axoneme of cilia and flagella.…”
Section: Microtubules (Mts) As Polyelectrolytes Acting As Electric Trmentioning
confidence: 98%
See 2 more Smart Citations